AN ANIMAL-STANDPOINT READING OF FAREWELL GUL’SARY BY CHINGIZ AITMATOV - Çetin, Gülsüm Tuğçe (My University, 2020)
As a sub-genre of ecocriticism, animal-standpoint criticism particularly traces the moral status of theanimals and therefore if they have any rights or not in the literary texts. Such a criticism also examines theworks of literature taking into consideration the ways animals are treated and what their roles or standpointsare. Animal-standpoint criticism, which has equal consideration for the animals at the core, rejects speciesism.In this respect, as a reflection of speciesism in literature, figurative use of the animals and the narration thatexcludes the animals’ condition and makes them not visible are criticized by such a criticism. In this context,Chingiz Aitmatov’s internalised writings, long before the theory had been constructed, dealing with nature andanimals are accepted as pioneer narrations. This study aims to examine the novel Farewell Gul’sary by ChingizAitmatov, considering the novel as a beyond time example in the respect of animal-standpoint criticism.
Keywords: Beşeri Bilimler; Ekoloji; Edebiyat; Felsefe